Editors: Mark S. Blooming, Jon F. Dee, Robert A. Taylor (London, 1998)
This book focus on the diagnosis and management of diseases and injuries in the working and sporting breeds. Includes: drug, physical examination, parasitology, treatment, reproduction, nutrition, and exercise and training
Keywords: Canine sports medicine,Working dogs; Disorders,Diseases